Theoretical Insights Into the Depolymerization Mechanism of Lignin to Methyl p-hydroxycinnamate by [Bmim][FeCl4] Ionic Liquid - Zhang, Tian; Zhang, Yaqin; Wang, Yanlei; Huo, Feng; Li, Zhangmin; Zeng, Qiang; He, Hongyan; Li, Xuehui (Frontiers in Chemistry, 2019)
Depolymerization of lignin into valuable aromatic compounds is an important starting point for its valorization strategies, which requires the cleavage of C-O and C-C bonds between lignin monomer units. The catalytic cleavage of these bonds is still difficult and challenging. Our previous experimental investigation (Green Chem., 2018, 20: 3743) has shown that methyl p-hydroxycinnamate (MPC) can be produced from molecular tailoring of H unit in lignin by the cleavage of the γ-O ester bond. In this study, the mechanism of [Bmim][FeCl4]-catalyzed depolymerization of lignin was investigated by using the density functional theory (DFT) method. The results reveal that [FeCl4]− anion of the catalyst plays a decisive role in the whole catalytic process, where two possible activation modes including three different potential reaction pathways can realize the depolymerization of lignin model compound. The calculated overall barriers of the catalytic conversion along these potential routes show that the third potential pathway, i.e., methanol firstly activated by [Bmim][FeCl4], has the most probability with the lowest energy barrier, while the second pathway is excluded because the energy barrier is too high. Also, the results illustrate that the solvent effect is beneficial to the reduction of the relative energy for the reaction to form the transition states. Hence, the obtained molecular level information can identify the favorable conversion process catalyzed by metallic ionic liquids to a certain extent, and it is desirable to enhance the utilization of biomass as a ubiquitous feedstock.